An active fault-tolerant control framework against actuator stuck failures under input saturations - Qi, Xin; Theilliol, Didier; He, Yuqing; Han, Jianda (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a control framework including active fault-tolerant control (FTC) and reference redesign is developed subject to actuator stuck failures under input saturations. FTC synthesis and reference redesign approaches are proposed to guarantee post-fault system safety and reference reachability. Then, these features are analyzed under both actuator stuck failures and constraints before fault-tolerant controller switches. As the main contribution, actuator stuck failures and constraints are unified so that they can be easily considered simultaneously.
Keywords: fault-tolerant control (FTC); actuator stuck failure; actuator constraints; reference redesign; linear matrix inequality (LMI)